Diat and Peace Money in the Crime of Culpable Homicide - Abu Hapsin; Nazar Nurdin (Al-Ahkam, 2022)
Islamic Law and Indonesian Criminal Law place compensation as an essential part of criminal liability. The fundamental difference is that compensation is primary in Islamic law, while positive law is an alternative. This paper examines and compares the application of the theory of diat and compensation in the crime of culpable homicide. The writing is framed with a normative-empirical approach, with data sources from books and court decisions. The results of the study show three things: First, diat and peace are different conceptions. Diat refers to property given in exchange for a slain soul, while peace is given as a compensation fee and as an effort to forgive. Second, the amount of compensation in the diat is regulated in detail with a certain nominal. At the same time, positive law is an agreement considering the perpetrator's ability. Third, compensation in the diat is an inspiration for developing legal theories such as restitutive justice, which emphasizes the importance of forgiveness and reconciliation between two parties. Research suggestions so that the diat theory can be developed into modern law so that it can be an inspiration for lawmakers so that in its application, the diat theory can be a reason for the abolition of crimes, not limited to leniency.